The neurosphere assay : an effective in vitro technique to study neural stem cells - Xapelli, Sara (2021)
© 2021, Wolters Kluwer Medknow Publications. This is an open access journal, and articles are distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 4.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as appropriate credit is given and the new creations are licensed under the identical terms